A merged kinetic mechanism study of two aviation surrogate fuels. (1st April 2021) - Tian, Dong-Xu; Liu, Yue-Xi; Wang, Bing-Yin; Tian, Zhen-Yu
Highlights: A universal mechanism including 1181 species and 6964 reactions was developed which could reproduce the oxidation and ignition delay times results of aviation fuels well. 3-C surrogate fuel tends to produce less pollutants. ROP and sensitivity analysis was carried out. Aromatics in surrogate fuels are important source of aromatics in products. H abstractions by OH are the main pathways of fuels consumption at low temperature region. However, H abstractions by H become more important as the temperature increasing. Abstract: A detailed chemical reaction kinetic mechanism involving 1181 species and 6964 reactions was developed for the combustion of two-components (surrogate A) and three-components (surrogate B) surrogate fuels for JP-8 and RP-3. The low temperature oxidation characteristics of the two surrogate fuels were compared regarding the aspects of components difference, negative temperature coefficient (NTC), intermediates and products formation. The surrogate A consists of 77.0% n-decane (NC10 H22 ) and 23.0% 1, 3, 5-trimethylbenzene (T135MB) by mole fraction. The composition of surrogate B is 66.2% n-dodecane (NC12 H26 ), 15.8% n-propylbenzene (NPB or A1C3 H7 ) and 18.0% 1, 3, 5-trimethylcyclohexane (T135MCH) by mole fraction. The initial reaction temperature, NTC temperature range and fuel depletion temperature of surrogate A are significantly lower than those of surrogate B. Surrogate A tends to produce more aromatics and oxygenates than surrogate B in terms of quantity and type. Acetaldehyde was observed in the oxidation of the two surrogate fuels, while methanol, ethanol, acrylaldehyde, 1-propanol, 2-propanol and acetone were only detected in surrogate A oxidation. According to ROP analysis, T135MB is consumed mainly by methyl abstraction reactions. However, consumption of NPB is dominated by decompositions on the propyl group. Sensitivity analysis indicates that the reactions H2 O2 (+M)<=>OH + OH(+M) and HO2  + HO2 <=>H2 O2  + O2 are the most promoting and inhibiting reactions on T135MB and NPB consumption. Moreover, the present mechanism could reproduce the ignition delay times of JP-8 and RP-3 surrogates. As the merged mechanism could simulate the macro and micro characteristics of fuel and surrogate fuel reasonably, it will be helpful to deepen the understanding of combustion process of aviation fuels.